Phage display creates innovative applications to combat hepatitis B virus - Tan, Wen Siang; Ho, Kok Lian (Baishideng Publishing Group, 2014)
Hepatitis B virus (HBV) has killed countless lives in human history. The invention of HBV vaccines in the 20th century has reduced significantly the rate of the viral infection. However, currently there is no effective treatment for chronic HBV carriers. Newly emerging vaccine escape mutants and drug resistant strains have complicated the viral eradication program. The entire world is now facing a new threat of HBV and human immunodeficiency virus co-infection. Could phage display provide solutions to these life-threatening problems? This article reviews critically and comprehensively the innovative and potential applications of phage display in the development of vaccines, therapeutic agents, diagnostic reagents, as well as gene and drug delivery systems to combat HBV. The application of phage display in epitope mapping of HBV antigens is also discussed in detail. Although this review mainly focuses on HBV, the innovative applications of phage display could also be extended to other infectious diseases.